2010
DOI: 10.1016/j.jpainsymman.2009.05.012
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Dying and Death Questionnaire (QODD): Empirical Domains and Theoretical Perspectives

Abstract: We used exploratory factor analysis within the confirmatory analysis framework, and data provided by family members and friends of 205 decedents in Missoula, Montana, to construct a model of latent variable domains underlying the Quality of Dying and Death (QODD) questionnaire. We then used data from 182 surrogate respondents, representing Seattle decedents, to verify the latent variable structure. Results from the two samples suggested that survivors’ retrospective ratings of 13 specific aspects of decedents’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
139
3
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(148 citation statements)
references
References 49 publications
2
139
3
4
Order By: Relevance
“…20 Despite its relevance to palliative care, existentialism as a theoretical perspective has been relatively absent within the literature. 21,22 Studies of carers' needs have been criticised more generally for their neglect of theory, 13,21 contributing to a degree of fragmentation within the literature. 23 Within psychology and psychotherapy, existentialism is concerned with the experiential conditions of human existence.…”
Section: Introductionmentioning
confidence: 99%
“…20 Despite its relevance to palliative care, existentialism as a theoretical perspective has been relatively absent within the literature. 21,22 Studies of carers' needs have been criticised more generally for their neglect of theory, 13,21 contributing to a degree of fragmentation within the literature. 23 Within psychology and psychotherapy, existentialism is concerned with the experiential conditions of human existence.…”
Section: Introductionmentioning
confidence: 99%
“…We chose a cut-off of 2 symptomatic episodes because patients with multiple symptomatic episodes are more likely to have a poor-quality death and have more to gain from symptom-reducing interventions. 24 We used χ 2 or 2-sample t-tests as appropriate for the bivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…We utilized two separate measures of quality of dying and death in our study, the singleitem QODD-1 and Total QODD scores based on recent work suggesting that neither measure provides an ideal measurement of QODD in isolation (Downey, Curtis, Lafferty, Herting, & Engelberg, 2010). In fact, the authors of the QODD study have noted that the Total QODD score has not been shown to be responsive to interventions, and along with other shortcomings, may not function as a cohesive construct of the quality of dying (Curtis et al, 2013).…”
Section: Discussionmentioning
confidence: 99%